Laparoscopic placement of left renal vein extravascular stenting in treatment of nutcracker syndrome: Techniques and long‐term outcomes. (20th September 2022) - Yu, Shuanbao; Cui, Jinshan; Liu, Junxiao; Du, Haopeng; Li, Peng; Fan, Yafeng; Tao, Jin; Dong, Biao; Li, Ziyao; Zhan, Yonghao; Wei, Yafei; Liao, Kexue; et al.
Abstract : Objectives: We aimed to assess the feasibility and efficacy of laparoscopic extravascular stent in treatment of nutcracker syndrome by transperitoneal or retroperitoneal approach. Methods: Seventy‐six patients with nutcracker syndrome were retrospectively enrolled from a tertiary referral center, and underwent transperitoneal (63 patients) or retroperitoneal (13 patients) laparoscopic extravascular stent from March 2011 to December 2020. Surgical parameters, complications, imaging and clinical outcomes were collected and analyzed. Results: All procedures were successfully carried out without open conversion. The median operation time, estimated blood loss, and postoperative hospital day were 120 (interquartile range [IQR]: 90–144) min, 20 (IQR: 10–30) ml, and 7 (IQR: 6–9) days. At a median follow‐up of 52 (range: 9–127) months, 60 (79%) patients had complete symptom resolution, 14 (18%) patients had significant symptom improvement, and 2 (3%) patients reported no symptom improvement. Ninety‐four percent (50/53) of hematuria, 91% (30/33) of proteinuria, and 89% (25/28) of flank/abdominal pain resolved after extravascular LRV stenting. No significant differences were detected in surgery parameters and recovery rates of clinical symptoms between two approaches (each p  > 0.05). However, patients with transperitoneal approach need longer to achieve complete recovery compared with retroperitoneal approach (8.7 vs. 1.5 months, p  = 0.016). Conclusions: Laparoscopic extravascular stent performed either transperitoneally or retroperitoneally is a feasible and effective option in treatment of nutcracker syndrome. Retroperitoneal laparoscopic extravascular stent required shorter time to achieve complete recovery, which should be considered whenever possible in surgical decision‐making.